Luperini, Romano (1999). «Il dialogo e il conflitto. Per un’ermenutica materialistica» - María de las Nieves Muñiz Muñiz (Swervei de publicacions, 1999)
Luperini, Romano (1999). Il dialogo e il conflitto. Per un’ermenutica materialistica